Evaluasi Kinerja Prodi Magister Pendidikan Ekonomi Melalui Tracer Study - Mintasih Indriayu; Sudarno Sudarno; Kristiani Kristiani; Harini Harini (Department of Economics Education, Universitas Sebelas Maret, 2018)
This study aims to find out (1) the existence of graduates and establish continuous communication and up date from graduates of the Masters in Economic Education; (2) identify competency profiles and skills of graduate stakeholders; (3) Knowing the relevance of implementing the curriculum to the needs of the labor market.The population of this tracer study activity is all graduates of the economic education master program from various generations and all companies / institutions / agencies / institutions both public or private where the graduates work. The samples used in this study are graduates who can be contacted face to face and via online (SMS, whatsapp, etc.)The results of the study are (1) The average length of alumni get a job for 5 months, while the old percentage of alumni get jobs <6 months by 69.57%, 6 - 12 months by 30.43%, and> 18 months by 0%; (2) Graduates work as lecturers at private universities as much as 30.43%, lecturers at state universities as much as 26.09%, teachers in government schools both civil servants and honorary teachers as much as 26.09%, teachers in private schools as much as 8.70%, government agencies as much as 4.35%, and private companies as much as 4.35%; (3) The alumni's work is 100% in accordance with the field of economic education; (4) Graduates constraints in finding work or while working are mastery in a foreign language (English), this is indicated by the results of a survey of 52.38% of graduates having difficulty finding work related to foreign language (English) mastery requirements. In addition, graduates who have worked also experienced the same thing, namely 71.74% said it was difficult to communicate in a foreign language (English); (5) Graduates provide input related to the learning process that should be carried out by MPE lecturers by way of discussion learning, this is indicated by the alumni's suggestion of 68.25% concerning discussion learning; (6) Graduates assess the canteen and photo facilities of coffee are less feasible to support lecture activities with a poor rating of 71.43%.